Uji Validitas dan Reliabilitas: Pemahaman Mahasiswa Akuntansi Terhadap Matakuliah Accounting For Business atau Pengantar Akuntansi - Hilda Salman Said; Chusnul Khotimah; Dekri Ardiansyah; Hanifah Khadrinur (Pusat Riset dan Inovasi Nasional, 2023)
Data collection tool using a questionnaire. The questionnaire used to assess accounting students' understanding of accounting in business courses must be valid and reliable. Validity is an index that shows that the measuring instrument measures the data correctly. The validity test can use the Pearson correlation technique for each score questionnaire and the total score questionnaire. The questionnaire instrument is said to be valid if the correlation value is positive and the probability value is less than the significant value of 0.05. The Cronbach's Alpha method is used to measure disappointment by showing that the questionnaire can be maintained and consistent, with the assumption that the questionnaire is said to be reliable if the Cronbach's Alpha value is more than the r table value. Based on the results of the validity test related to accounting students' understanding of accounting for business courses, it was explained that the questionnaire instruments related to assets, liabilities, and equity proved valid because they had a significant value on a validity test of less than 0.05, while the question instruments related to liabilities were not reliable.